Expression of phoenixin-14 and nesfatin-1 in the hypothalamo-pituitary-gonadal axis in the phases of the estrous cycle - Ak, Tuba Parlak; Yaman, Mine; Bayrakdar, Ali; Bulmus, Ozgur (Elsevier, 2023)
Phoenixin-14 (PNX-14) and nucleobindin 2 (NUCB2)/nesfatin-1 are regulatory neuropeptides expressed in the hypothalamus. These neuropeptides can be effective in hormonal regulation of the hypothal-amo-pituitary-gonadal (HPG) axis and reproductive functions. In the present study, the distribution of PNX-14 and NUCB2/nesfatin-1 in the hypothalamus, pituitary, ovary, and uterus tissues during the phases of the estrous cycle in female rats was investigated. Eighteen Wistar Albino rats determined among animals showing regular estrous cycle by vaginal smear method were divided into three groups: proestrus (Group I), estrus (Group II) and diestrus (Group III). Serum gonadotropin-releasing hormone (GnRH), plasma PNX-14, and NUCB2/nesfatin-1 concentrations were the highest, moderate, and lowest in estrus, diestrus, and proestrus phases, respectively. PNX-14 immunoreactivity in the supraoptic and arcuate nuclei of the hypothalamus and NUCB2/nesfatin-1 immunoreactivity in the paraventricular nuclei were particularly evident in the estrus phase. These neuropep-tide immunoreactivities were decreased in different cells of anterior pituitary during proestrus compared with those during estrus and diestrus. PNX-14 immunoreactivity in the ovary, especially during the estrus phase, was diffuse and intense in the granulosa and luteal cells and oocytes, and it was few and weak in theca cells. In addition, NUCB2/nesfatin-1 immunoreactivity was abundant and strong in granulosa and luteal cells, theca and interstitial cells, and oocytes during estrus. In the estrus phase, PNX-14 immunoreactivity was strong in the glandular epithelial cells and stromal cells of the endometrium, also NUCB2/nesfatin-1 immunoreactivity was strong in the epithelial and glandular epithelial cells. As a result, when the estrous cycle was evaluated, it was concluded that the changes in the distribution of PNX-14 and NUCB2/nesfatin-1 at all phases were related to GnRH and that these neuropeptides showed the highest immunoreactivity especially in the HPG axis and uterus tissues of estrus rats.
Keywords: Estrous cycle; Nucleobindin 2 (NUCB2); nesfatin-1; Phoenixin-14; Rat